2019
DOI: 10.1380/ejssnt.2019.130
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Science Approach to Unveiling the TiO<sub>2</sub> Photocatalytic Mechanism: Correlation between Photocatalytic Activity and Carrier Lifetime

Abstract: Establishing an accurate view of the photocatalytic mechanism of titanium dioxide (TiO2) has been a challenging task since the discovery of the Honda-Fujishima effect. Despite the great success of catalytic studies in elucidating the chemical and physical aspects of photocatalysis, many questions remain. A surface science approach, which is characterized by the use of atomically well-defined surfaces in precisely controlled environments, is a powerful tool to shed light on the fundamental mechanism, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 88 publications
1
16
0
Order By: Relevance
“…Previous results suggested that a bulk O V and surface O V play different roles. [68][69][70][71][72] It was proposed that the surface O V can trap the photoexcited electrons. Furthermore, the electron and hole can be separated due to the surface band bending and the e-h recombination is suppressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results suggested that a bulk O V and surface O V play different roles. [68][69][70][71][72] It was proposed that the surface O V can trap the photoexcited electrons. Furthermore, the electron and hole can be separated due to the surface band bending and the e-h recombination is suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the electron and hole can be separated due to the surface band bending and the e-h recombination is suppressed. 69,70 Moreover, the surface O V is also known as a chemically reactive site, which can improve the photocatalytic properties. 17,18 However, on the other hand, there are many reports showing that the bulk O V acts as an e-h recombination center, 68,[72][73][74][75] which is in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…[46,47] This difference is based on the fact that the energy band structures of anatase and rutile phase crystals exhibit an indirect bandgap and a direct bandgap, respectively. [48,49] The direct bandgap structure of rutile phase crystal allows the photoexcited charge carriers to easily recombine each other with the emission of photons. In contrast, the indirect bandgap structure of anatase phase crystal allows the photoexcited charge carriers to recombine each other with the assistance of phonons.…”
Section: Discussionmentioning
confidence: 99%
“…This assistance of phonons suggests that the photogenerated electrons in the anatase phase crystal do not directly recombine the photogenerated holes, extending the photoexcited carrier lifetime and increasing the photoexcited carrier concentration. [48,49] Thus, the phase transformation to the anatase phase would contribute to the enhanced photoexcited carrier concentration under UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Surface indices of rutile TiO 2 were wrongly displayed in Table 3 in the original article [1]. The correct table is shown below.…”
mentioning
confidence: 99%